4CPS-144 Effectiveness and safety of induction therapy with vedolizumab in patients with intestinal inflammatory disease - Muñoz, C Gallego (Eur J Hosp Pharm, 2018)
BACKGROUND: Vedolizumab is a therapeutic alternative indicated in patients with moderate-severe inflammatory bowel disease (IBD) (ulcerative colitis (UC) and Crohn’s Disease (CD)) with loss of response or intolerance to first-line treatment. PURPOSE: To evaluate the effectiveness and safety of induction treatment with vedolizumab in patients diagnosed with IBD. MATERIAL AND METHODS: Observational retrospective study was conducted from February 2016 to September 2017. Patients with IBD who had received treatment with vedolizumab were included. Variables collected were: demographic (age, sex), clinical (time from diagnosis to the start of treatment with vedolizumab, number of prior anti-TNFα), related to effectiveness (variation of corticosteroid doses, haemoglobin, c-reactive protein, faecal calprotectin and number of stools from week 0 to week 6) and related to safety (adverse events). Variables related to effectiveness were measured at week 0 and week 6. Student’s t-test (SPSS 20.0) was used to quantify the variation in the analytical parameters. RESULTS: We included 19 patients (53% malea), with a mean age of 46 (SD: 16) years, treated with vedolizumab. Eleven of them presented the diagnosis of CU. The mean number of months from diagnosis to start with vedolizumab was 83 (SD: 79). 15.8% were not treated with any anti-TNFα previously, 10.5% with infliximab, 68.4% with infliximab and adalimumab, and 5.3% with infliximab, adalimumab and golimumab. The reason to begin vedolizumab treatment was a previous loss of response to anti-TNF in 84.2% of patients. Of the 14 patients being treated concomitantly with corticosteroids, the dose was reduced in 71.4% of them. There were no statistically significant differences in faecal calprotectin, haemoglobin, c-reactive protein levels (p>0.05) at week 6 compared to baseline level. 18.2% patients had a decrease in the number of stools. Only two patients presented adverse events associated with the treatment (skin reactions). CONCLUSION: Vedolizumab has been shown to be effective and safe in our patients during the induction period, allowing a reduction in corticoid doses and the number of stools, improving the quality of life of our patients. However, there were not any differences in the analytical parameters. REFERENCES AND/OR ACKNOWLEDGEMENTS: My gratitude to the general hospital Reina Sofia and the people who helped me to conduct the study No conflict of interest